Literature as a Medium of Exposing Social Problem through Thomas Grayâ€™s â€œElegy Written in A Country Churchyardâ€ - Manugeren, M; Suhadi, Jumino; pardi, pardi (Universitas Sanata Dharma, 2020)
Apart from being an entertainment medium, literature has also an important role in exposing social problems, as basically literature is born and is intended for the community. Through the disclosure of social problems, the role of literature is increasingly developing, among others, as a medium of teaching, reference, reflection, character building and also criticism. Thus, it is clearly illustrated that literature has multifunctional roles. The message conveyed through literature can be effectively absorbed by the community owing to the entertainment factor. Through the poem â€œElegy Written in a Country Churchyardâ€, Thomas Gray tells the story of the lives of marginal people, always having to face problems. Through descriptive qualitative research method, referring to social phenomena, supported by sociology of literature approach, the results of the study show that there are three social problems that always arise in the community, especially in the lower class one: poverty, right to get proper education and equality to obtain opportunities in the line of life. These three social problems are closely interrelated so that they become a unification undermining the lives of marginalized people.